Cardio-respiratory and biochemical responses of military training event at Jungle environment - Yadav, Angad; Chatterjee, Tirthankar; Bhattacharyya, Debojyoti; Singh, Somnath; Pal, Madhusudan (Asian Journal of Medical Sciences, 2021)
Background: In military environment, soldiers regularly practice or undergo different types of extreme training activities. However, globally the literatures available on the physiological and biochemical demand of different extreme military training activities are very scanty and less reported. Aims and Objective: The present study was undertaken to quantify the cardio-respiratory and biochemical responses of military training event in jungle environment. Materials and Methods: Mathew’s Mad Mile (MMM) activity is a type of specialized run of 1.5 mile in jungle environment. This training activity was conducted on rugged jungle terrain comprised of undulated uphill, downhill, muddy surface. Twenty-five SHAPE-1 healthy soldiers were volunteered into training event. Cardiorespiratory data was recorded continuously throughout the event and venous blood sample was drawn before and immediately after completion of the event. Statistical significance was considered at p<0.05. Results: There was no significant difference observed in heart rate and breathing rate while core body temperature was significantly (p = 0.02) higher in slow finisher as compared to fast finisher. In fast finisher, post exercise level of BDNF, BNP, SDH, cortisol and UCP1 increased significantly (p<0.05), whereas, BHB (p<0.01) decreased significantly in comparison to pre-exercise. In slow finishers, post exercise level of cortisol, KYNA and UCP1 increased significantly (p<0.05), whereas, BDNF, BNP and SDH decreased significantly (p<0.05), in comparison to pre-exercise. Conclusion: The outcome of this study indicated that the slow finishers were more susceptible to risk of injury due to higher exercise induced thermogenesis and mental stress in comparison to fast finisher.